Altered neural correlates of episodic memory for food and non-food cues in females with overweight/obesity. (1st August 2022) - Leng, Xuechen; Huang, Yufei; Zhao, Song; Jiang, Xintong; Shi, Pan; Chen, Hong
Abstract: Episodic memory formation is fundamental to cognition and plays a key role in eating behaviors, indirectly promoting the maintenance and acceleration of weight gain. Impaired episodic memory function is a hallmark of people with overweight/obesity, nevertheless, little research has been conducted to explore the effects of overweight/obesity on neural networks associated with episodic memory. The current study aimed to unravel the behavioral responses and neurocognitive mechanisms underlying the episodic memory for food and non-food cues in females with overweight/obesity. To explore this issue, a group of females with overweight/obesity ( n  = 26) and a group of age-matched females with healthy weight ( n  = 28) participated in a functional magnetic resonance imaging (fMRI) event-related episodic memory paradigm, during which pictures of palatable food and pictures of neutral daily necessities were presented. Whole-brain analyses revealed differential engagement in several neural regions between the groups during an episodic memory task. Specifically, compared to the healthy weight controls, females with overweight/obesity exhibited reduced brain activity in the temporal, parietal, and frontal regions during episodic memory encoding and successful retrieval of both food and non-food cues. Additionally, activation patterns in the left hippocampus and right olfactory cortex of females with and without overweight/obesity suggested that item memory changed according to the type of stimuli presented during item memory. Specifically, females with overweight/obesity showed greater engagement of the left hippocampus and right olfactory cortex when processing food cues, but less activation of the left hippocampus and right olfactory cortex when presented with non-food cues. Consistent with the obesity and suboptimal food-related decision theoretical model, these findings provide evidence of dissociation of the neural underpinnings of episodic memory in females with overweight/obesity and underline important effects of overweight/obesity on brain functions related to episodic memory.